2021
DOI: 10.3390/metabo11060402
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine: A Metabolite to Be Targeted in Cancers

Abstract: Amino acids play central roles in cancer progression beyond their function as building blocks for protein synthesis. Thus, targeting amino acid acquisition and utilization has been proved to be therapeutically beneficial in various pre-clinical models. In this regard, depletion of circulating asparagine, a nonessential amino acid, by L-asparaginase has been used in treating pediatric acute lymphoblastic leukemia (ALL) for decades. Of interest, unlike most solid tumor cells, ALL cells lack the ability to synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 86 publications
(108 reference statements)
1
52
0
1
Order By: Relevance
“…Asparagine, a nonessential amino acid, plays an important role in cancer cell proliferation, supporting cell survival under glutamine deprivation, electron transport chain inhibition, and metastasis in solid tumors [ 28 ]. Mechanistically, asparagine functions as an exchange factor for the uptake of other essential amino acids, stimulating mTORC1 signaling and nucleotide biosynthesis [ 29 , 30 ].…”
Section: Asparaginementioning
confidence: 99%
“…Asparagine, a nonessential amino acid, plays an important role in cancer cell proliferation, supporting cell survival under glutamine deprivation, electron transport chain inhibition, and metastasis in solid tumors [ 28 ]. Mechanistically, asparagine functions as an exchange factor for the uptake of other essential amino acids, stimulating mTORC1 signaling and nucleotide biosynthesis [ 29 , 30 ].…”
Section: Asparaginementioning
confidence: 99%
“…A key player in driving the resistance to L-ASNase treatment is the expression of asparagine synthetase (ASNS), the rate-limiting enzyme for de novo biosynthesis of L-asparagine [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the expression of ASNS itself, studies suggest that the availability of aspartate and glutamine, two indispensable substrates of ASNS, are also important for the cellular adaptation to the depletion of exogenous asparagine [67,68]. In cell culture conditions, most cancer cells can use glutamine to synthesize aspartate de novo.…”
Section: Discussionmentioning
confidence: 99%
“…Tucci et al (40) clarified that ALL cells accelerate adipocyte lipolysis and use the produced FFA to complement lipogenesis and de novo proliferation. In another study, Chronic Lymphocytic Leukemia (CLL) cells, in comparison with normal B lymphocytes, are able to catabolize lipids that allows usage of FFAs for oxidative respiration (41). FFAs also can interact with the nuclear receptor peroxisome proliferator-activated receptor a (PPARa).…”
Section: Fatty Acid Metabolism In Leukemic Stem Cellsmentioning
confidence: 99%
“…Orgel et al (43) showed that glutamine secreted by adipocytes protects leukemia cells from treatment with L-asparaginase. This is especially true, considering that L-asparaginase is used in the treatment of ALL, because leukemic lymphoblasts are quite sensitive to exogenous asparagine and glutamine depletion (41,43).…”
Section: Fatty Acid Metabolism In Leukemic Stem Cellsmentioning
confidence: 99%